Perceptions of Media Roles in Serbia and Croatia: Does News Orientation Have an Impact?. (3rd October 2019) - Pjesivac, Ivanka; Imre, Iveta
ABSTRACT: This study examined the perceptions of media roles among journalism students in Serbia and Croatia ( N  = 401). The results showed that the most important were citizen-oriented and watchdog roles and that they were positively predicted by hard news orientation, whereas consumer and loyal roles were least important. Consumer role was positively predicted by the soft news orientation, whereas the best predictor for the perceptions of the loyal media role was political orientation (right of the center). This is the first study that comparatively analyzed students' views in two countries of the former Yugoslavia using national samples.